Robot golf bag carrier - Mohd Shahrawi Bin Abdul Ghapar (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2015)
Golf is a one of most popular sport in the world, various equipment are used in the game golf like a variety of golf clubs, golf balls, bags and the average amount for all the equipment around 10 kg to 15 kg. From the observation and analysis, the sport of golf is still lacking in terms of transport innovation for transporting golf equipment from one place to another because golf requires us to move in the long distance during playing, excessive loads may cause pain in the spine, arms and shoulders. Players can use the services caddy to bring golf equipment but must pay the high charges and caddy required a long time to bring equipment from one hole to the other hole. Therefore, robot golf bag carrier are designed, this robot is innovation from trolley and capable replace caddy service. Robot golf bag carrier using a direct current motor 6 V 1200 rpm in both wheels to move the robot and carry the load placed on the robot, control device for controlling the movement of the robot, 6 V battery as source of power to drive the robot, control circuit and body structure robot is lightweight and made from aluminum to cover the burden of robot are brought. Weight of robot about in 10kginclude with two DC motor. Step to use a golf bag carrier robot is to turn on the switch, put the golf equipment on the robot and control the robot using the controller.